Dhanyang dan Prewangan: Kuasa Roh Halus dalam Dunia Mistik Orang Jawa Perantau di Dataran Tinggi Gayo - Shadiqin, Sehat Ihsan; Fuadi, Tuti Marjan (Jurnal Sosiologi USK (Media Pemikiran & Aplikasi), 2023)
The purpose of this study is to investigate how members of disadvantaged communities imagine "other lives," and how such perceptions influence their own lives. This study will explore how society defines things that are unseen but are believed to exist and may impact human existence by having a look at the overseas Javanese population in the Gayo highlands in Aceh. The findings of this study will be used to illustrate how society views these creatures. This study, in contrast to the majority of other studies of overseas Javanese, is interested in how the construction efforts of danyang and prewangan are and how they communicate with each other. Other studies of overseas Javanese focus on topics such as cultural assimilation, conflict, and resilience. The information needed for this study was gleaned through participant observation and in-depth interviews with local Javanese residents of Aceh's Bener Meriah District. Because of the economic and cultural marginalization they face when interacting with the dominant ethnic groups of Gayo and Aceh, which persuades them to seek alternative protection, this article demonstrates that the concepts of danyang and prewangan are part of the identity that was brought from Javanese culture.